Twice Daily Prazosin and Valproic Acid in the Treatment of Flashbacks in PTSD - Kristy A. Fisher; Heidi Kiziah; Clara L. Villalba Alvarez (Case Reports in Psychiatry)
Posttraumatic stress disorder (PTSD) is a debilitating stress disorder occurring in the context of a traumatic event and is characterized by intrusive and avoidance symptoms, negative alterations in cognition and mood, and arousal and reactivity changes. Despite its representation throughout literature, the pathophysiology of PTSD remains incompletely understood, thus contributing to broad, variable, and at times, experimental treatment options. The authors present the first documented case of the rapid and successful management of PTSD using valproic acid and twice daily dosing of prazosin aimed at targeting symptoms of hyperarousal and both daily and nightly intrusive symptoms of flashbacks and nightmares, respectively. The authors also discuss postulations of the underlying mechanisms of action responsible for such symptom alleviation. Further investigation is needed to expand upon our knowledge of the use of such agents in the treatment of PTSD to improve upon existing clinical guidelines, especially in the acute setting, thus providing better overall prognosis.